2016
DOI: 10.3389/fncir.2016.00105
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Synaptic Plasticity in L-DOPA-Induced Dyskinesia

Abstract: The emergence of L-DOPA-induced dyskinesia (LID) in patients with Parkinson disease (PD) could be due to maladaptive plasticity of corticostriatal synapses in response to L-DOPA treatment. A series of recent studies has revealed that LID is associated with marked morphological plasticity of striatal dendritic spines, particularly cell type-specific structural plasticity of medium spiny neurons (MSNs) in the striatum. In addition, evidence demonstrating the occurrence of plastic adaptations, including aberrant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…This difference in neuromodulation can influence synaptic activity. For example, the chronic DA deficiency observed in PD models is often accompanied by changes in synaptic plasticity or altered cellular physiology (Calabresi et al, 2009; Surmeier et al, 2014; Wang and Zhang, 2016; Zhai et al, 2018; Graves and Surmeier, 2019). Thus, the ability to simultaneously assess tonic and phasic changes in dopamine release in freely-behaving animals represents a tremendous advance for the field.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in neuromodulation can influence synaptic activity. For example, the chronic DA deficiency observed in PD models is often accompanied by changes in synaptic plasticity or altered cellular physiology (Calabresi et al, 2009; Surmeier et al, 2014; Wang and Zhang, 2016; Zhai et al, 2018; Graves and Surmeier, 2019). Thus, the ability to simultaneously assess tonic and phasic changes in dopamine release in freely-behaving animals represents a tremendous advance for the field.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with short half-life medicine, such as L-dopa, is connected with fluctuating plasma levels of the drug and subsequent oscillations in synaptic dopamine concentrations (Abbruzzese et al, 2012). Over time, this changeability is supposed to induce maladaptive changes in basal ganglia motor circuits, resulting in LID development (Wang and Zhang, 2016). Therefore, continuous delivery of L-dopa is helpful in reducing the emergence of the LID phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a task related fMRI trial it has been shown that levodopa intake induces a hyperactivity of the pre-SMA in the NoGo condition only in the dyskinetic patients (Herz et al 2014b), whereas the resting state functional connectivity between MC/SMA (+pre-SMA) and putamen is decreased after levodopa ingestion in LID (Herz et al 2016). Also, it has been proposed that LID are caused by a maladaptive synaptic plasticity (Wang and Zhang 2016). Using a continuous theta burst stimulation protocol Huang and co-workers demonstrated in PD patients that dopamine is required to induce long term potentiation (LTP), and that depotentiation could subsequently not be induced in the subset of patients suffering from LID (Huang et al 2011).…”
Section: Pre-sma-putaminal Functional Connectivitymentioning
confidence: 99%